From Traditional to Digital: Barriers and Opportunities for Small Traders in the Post-Pandemic - Mu’arofah, Afrila; Fuad, A. Zaky (Commodities, Journal of Economic and Business, 2024)
This study examines the digital transformation of Warujayeng Market, a traditional rural market in Indonesia, focusing on the barriers and opportunities faced by small traders during post-pandemic recovery. While existing literature predominantly analyzes urban and formal sector digitalization, this research addresses critical gaps by investigating how socio-cultural factors shape technology adoption in informal rural markets. Employing a mixed-methods approach combining longitudinal surveys (n=127), ethnographic observations, and platform analytics, the study reveals three key findings: (1) digital adoption follows nonlinear, kinship-mediated pathways rather than conventional diffusion patterns; (2) traders develop innovative hybrid practices ("digital bricolage") that blend mobile technologies with traditional commerce; and (3) current policy approaches underestimate cultural barriers while overestimating technological readiness. The findings contribute a new Sociocultural Technology Adaptation Model (STAM) and offer practical recommendations for context-sensitive digital development strategies in traditional market ecosystems.